An evaluation of Universiti Teknologi MARA Cawangan Pahang website regarding to its acceptance among staff / Mohd Amli Abdullah Baharum ... [et al.] - Abdullah Baharum, Mohd Amli; Rashid, Zarina Zainul; Husin, Zuhariah; Abu, Zurah; Sahat, Sa'diah (2011)
Website is a one stop terminal to a large volume of information and organizations websites have long been one of the important communication medium for relaying and providing information and interaction tool between staff, stakeholders and the organization. As such, this study is undertaken to evaluate Universiti Teknologi MARA (UiTM) Pahang website and its acceptance among staff based on the following four basic attributes namely: user friendliness; informativeness; suitability, and attractiveness. The research was conducted to evaluate the staff acceptance on the criteria of good website and to recommend actions to be taken to improve the website. An unsupervised questionnaire survey using 5 likert scale were distributed to all staff in UiTM Pahang. The questionnaires compose of part A with demographic profile and part B relates to acceptance towards campus website. The data were analyzed using descriptive statistics. The findings show that user friendliness, informativeness and attractiveness falls within a good range whereas suitability is found to be satisfactory. Only 72% of the UiTM Pahang staff inclined to recommend the websites to their friends. Actions need to be taken to improve the website by incorporating more online services, creating more attractive design and making available latest information among others.